Catalytic asymmetry in homodimeric h+‐pumping membrane pyrophosphatase demonstrated by non‐hydrolyzable pyrophosphate analogs - Anashkin Viktor A.; Malinen Anssi M.; Bogachev Alexander V.; Baykov Alexander A. (MDPI, 2022)
Membrane-bound inorganic pyrophosphatase (mPPase) resembles the F-ATPase in catalyzing polyphosphate-energized H+ and Na+ transport across lipid membranes, but differs structurally and mechanistically. Homodimeric mPPase likely uses a “direct coupling” mechanism, in which the proton generated from the water nucleophile at the entrance to the ion conductance channel is transported across the membrane or triggers Na+ transport. The structural aspects of this mechanism, including subunit cooperation, are still poorly understood. Using a refined enzyme assay, we examined the inhibition of K+-dependent H+-transporting mPPase from Desulfitobacterium hafniensee by three non-hydrolyzable PPi analogs (imidodiphosphate and C-substituted bisphosphonates). The kinetic data demonstrated negative cooperativity in inhibitor binding to two active sites, and reduced active site performance when the inhibitor or substrate occupied the other active site. The nonequivalence of active sites in PPi hydrolysis in terms of the Michaelis constant vanished at a low (0.1 mM) concentration of Mg2+ (essential cofactor). The replacement of K+, the second metal cofactor, by Na+ increased the substrate and inhibitor binding cooperativity. The detergent-solubilized form of mPPase exhibited similar active site nonequivalence in PPi hydrolysis. Our findings support the notion that the mPPase mechanism combines Mitchell’s direct coupling with conformational coupling to catalyze cation transport across the membrane.